Intersections of judicial collective redress and corporate restructuring law:: Case studies of English mass tort restructurings - Tavakolnia, Arwin (European Insolvency and Restructuring Journal, 2025)
Two rapidly developing fields of private law - corporate restructuring law on the one hand and judicial collective redress on the other - may intersect. The two distinct legal spheres intersect when a distressed but viable corporate defendant initiates a restructuring procedure to resolve its mass tort liability with as much finality as possible. These so-called mass tort restructurings are already common in the U.S., a pioneer in both restructuring law and collective redress. But mass tort restructurings are not limited to the U.S. borders. This article provides an overview of mass tort restructurings in England and Wales based on presently documented case law. These English case studies provide a unique perspective on mass tort restructurings and may thereby contribute to a broader EU-wide policy debate on such restructurings in general.